Una Exploración Conceptual de la Formación de Patrones en Sistemas Sociales Autorganizados - Anzola, David (Ingeniería, 2018)
Context: The concept of self-organization plays a major role in contemporary complexity science. Yet, the current framework for the study of self-organization is only able to capture some of the nuances of complex social self-organizing phenomena. Method: This article addresses some of the problematic elements in the study of social selforganization. For this purpose, it focuses on pattern formation, a feature of self-organizing phenomena that is common across definitions. The analysis is carried out through three main questions: where can we find these patterns, what are these patterns and how can we study these patterns. Results: The discussion shows that there is a high level of specificity in social self-organized phenomena that is not adequately addressed by the current complexity framework. It argues that some elements are neglected by this framework because they are relatively exclusive to social science; others, because of the relative novelty of social complexity. Conclusions: It is suggested that interdisciplinary collaboration between social scientists and complexity scientists and engineers is needed, in order to overcome traditional disciplinary limitations in the study of social self-organized phenomena.